8+4(3c-1) how to solve

Just expand using Distributive law , and Simplify:

8 + 4 ( 3c - 1 ) =

8 + 12c - 4 =

12c +4

8+4(3c-1) how to solve

Tutors, please sign in to answer this question.

Woodland Hills, CA

Just expand using Distributive law , and Simplify:

8 + 4 ( 3c - 1 ) =

8 + 12c - 4 =

12c +4

- Math Help 5452
- Algebra 5059
- Math Word Problem 4502
- Calculus 2207
- Word Problem 5121
- Algebra 2 3504
- Algebra 1 4075
- Math Problem 1019
- Math Help For College 1400
- Math Equations 957